Comparison Study on the Relative Rates in Heat-Driven Oxidation of PUFAs - Huafeng Lin, Haizhen Wang, Qiudi Deng, Xin Yuan, Xinming Lei, Aimin Deng, Xiangwen Peng (Forest Chemicals Review, 2021)
Fish oil and fish meal are rich in polyunsaturated fatty acids (PUFAs) which are readily subjected to oxidative deterioration under conditions of increasing temperature and prolonged time. The purpose of the present study was to evaluate the oxidative degradation of PUFAs in fish oil and fishmeal under condition of continuous oven heating at 105 ± 2°C. In this experiment, sampling time for fish oil was set to 0 h, 12 h, 24 h, 36 h, 48 h, 72 h, 84 h, and that for fishmeal was set to 0 h, 12 h, 24 h, 36 h, 48 h, 60 h, 72 h, 84 h, 96 h, and 108 h. The oxidative degradation rates of PUFAs in fish oil and fish meal were evaluated by monitoring the variations of fatty acid compositions with gas chromatography (GC) spectrometry. Data analysis showed that PUFAs (including DHA and EPA) tend to oxidatively decompose at a varying rate in fish oil--under accelerated oxidation conditions, PUFAs in fish oil were oxidated violently within 36 h, and then, their oxidative rates were lowered down gradually to be approximately constant. However, for fishmeal, the oxidative rates of PUFAs were basically linearly proportional to the test time within a period of 108 h. We further deduced that non-lipid compounds (e.g. proteins, nucleic acids and carbohydrates) in fishmeal, acting as protective factors, prevent the oxidation of PUFAs through the mechanism of solid absorbing thermal energy.